1973
DOI: 10.1103/physrevc.7.930
|View full text |Cite
|
Sign up to set email alerts
|

Renormalization of the Axial-Vector Coupling Constant in NuclearβDecay

Abstract: to one's convenience. For small A, the wave function does not seem to be so nearly factorable and solving Eq. (2V) should lead to an improvement in both the energy and the wave function.In summary, we point out that a continuous class of transformations (for generating a state which is an eigenstate of the total momentum from a state which is not) have been presented. Of this class, the transformation which minimizes the energy is the transformation characterized by the function G which sa'tisf led Eq. (2V). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

1975
1975
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 25 publications
3
50
0
Order By: Relevance
“…Thus, X is in principle not a constant over the whole range of nuclei. For light nuclei, a deviation of X from the free-nucleon value by 17% has been found Szybisz, 1975;(Wilkinson, 1973a, 1974aAEricson et al,, 1973Ohta and Wakamatsu, 1974), Under these assumptions, we develop the relation between form-factor coefficients and nuclear matrix elements for a pure V-A nucleon current of the form given in Eq. (2-4).…”
Section: -Mf M M Ilmentioning
confidence: 98%
“…Thus, X is in principle not a constant over the whole range of nuclei. For light nuclei, a deviation of X from the free-nucleon value by 17% has been found Szybisz, 1975;(Wilkinson, 1973a, 1974aAEricson et al,, 1973Ohta and Wakamatsu, 1974), Under these assumptions, we develop the relation between form-factor coefficients and nuclear matrix elements for a pure V-A nucleon current of the form given in Eq. (2-4).…”
Section: -Mf M M Ilmentioning
confidence: 98%
“…The first type of quenching depends strongly on the size of the model space used in the calculation and is thus model dependent. It was extensively investigated in light nuclei, A ∼ 20, in the 1970s [65][66][67] within the framework of the ISM where it was found that g A,ef f ∼ = 1.0, q ∼ = 0.75. In heavy nuclei, of particular interest in this paper, the ques-tion of quenching was first discussed by Fujita and Ikeda [68] in 1965.…”
Section: νββ Decay a Matrix Elementsmentioning
confidence: 99%
“…However, it is also well established [30,43] that in the shell model, up to a good approximation, the phenomenon can be taken into account by an empirical multiplicative factor, (g A /g V ) eff = λ (g A /g V ) bare with a bare value for the ratio of 1.26 as obtained from neutron decay (see Ref. [44] for certain cautions).…”
Section: A Effective Gt-operatormentioning
confidence: 99%